Evaluation of Teacher's Pedagogical Competence in Developing 2013 Curriculum Learning - Lalu Hendra Wijaya; Maimun Sholeh; Mispandi Mispandi (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2021)
This study aims to examine the standard process for preparing the 2013 curriculum lesson plans, the teacher's ability in preparing the 2013 curriculum lesson plans, and the guidelines used in the preparation of the 2013 curriculum RPP. Data collection techniques by means of observation, interviews, and documentation. The data analysis technique uses inductive qualitative data analysis. Data analysis was carried out using data analysis techniques proposed by Miles and Huberman which included data reduction, data display, and conclusion drawing. The results showed that the RPP preparation process must follow the standards the drafting process, and the existing rules or guidelines published by the government, then the teacher's ability to compile the 2013 curriculum lesson plan can be said to be